Pengaruh edukasi perawatan kaki terhadap pengetahuan cara merawat kaki klien diabetes melitus - Salsabilla, Schatzi Fiore; Salmiyati, Suri; Rahmawati, Agustina (JOURNAL OF Community Health Issues, 2025)
Background: Diabetes mellitus is a chronic disease of carbohydrate, protein and fat metabolism disorders that can be characterized by increased blood glucose or blood sugar levels. Diabetes mellitus can cause peripheral neuropathy such as diabetic ulcers. Diabetic ulcers can attack the lower extremities (feet) of patients. Purpose: To determine the effect of foot care education on knowledge of how to care for feet in clients with diabetes mellitus. Method: This study was quantitative with an design (pre-experimental) one group pretest -posttest. The sample in this study consisted of 35 diabetes mellitus patients who were selected using random sampling techniques in prolanis activities at Puskesmas 1 Sentolo. Data were collected using a questionnaire on knowledge of how to care for feet. Data analysis was performed using the Wilcoxon test. Results: The study showed the effect of foot care education on knowledge of how to care for the feet of clients with diabetes mellitus, with a p-value of 0.000 (p <0.05). Conclusion: Foot care education can broaden the knowledge of clients with diabetes mellitus after receiving foot care education. It is hoped that clients with diabetes mellitus will practice foot care to prevent potential complications of diabetic ulcers. Keywords: Diabetes Mellitus; Foot Care; Ulcers. Pendahuluan: Diabetes melitus merupakan penyakit kronis gangguan metabolisme karbohidrat, protein dan lemak yang dapat ditandai dengan adanya peningkatan kadar glukosa darah atau gula darah. Penyakit diabetes melitus dapat menyebabkan neuropati perifer seperti ulkus diabetikum. Ulkus diabetikum dapat menyerang pada ekstremitas bawah (kaki) pasien Tujuan: Untuk mengetahui pengaruh edukasi perawatan kaki terhadap pengetahuan cara merawat kaki pada klien diabetes melitus. Metode: Penelitian kuantitatif dengan desain pre-experimental one group pretest -posttest. Sampel pada penelitian ini terdiri dari 35 pasien diabetes melitus yang terpilih menggunakan teknik random sampling dalam kegiatan prolanis di Puskesmas 1 Sentolo. Data dikumpulkan menggunakan kuesioner pengetahuan cara merawat kaki. Analisis data dilakukan menggunakan uji wilcoxon. Hasil: Adanya pengaruh edukasi perawatan kaki dengan pengetahuan cara merawat kaki klien diabetes melitus, dengan nilai p-value 0.000 ( p < 0.05). Simpulan: edukasi perawatan kaki dapat menambah luas wawasan pengetahuan klien diabetes melitus setelah diberikan edukasi perawatan kaki. Kata Kunci: Diabetes Melitus; Perawatan Kaki; Ulkus.